Hollow Co0.85Se nanowire array on carbon fiber paper for high rate pseudocapacitor - Banerjee, Abhik; Bhatnagar, Sumit; Upadhyay, Kush Kumar; Yadav, Prasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2014)
A supercapacitor electrode is fabricated with Co0.85Se hollow nanowires (HNW) array, which is synthesized by wet chemical hydrothermal selenization of initially grown cobalt hydroxyl carbonate nanowires on conductive CFP. The dense self-organized morphology of Co0.85Se HNWs is revealed by scanning/transmission electron microscopy. The as-synthesized Co0.85Se HNWs possess high pseudocapacitive property with high capacitance retention and high durability. The areal capacitance value is seen to vary from 929.5 to 600 mF cm(-2) (60% retention) as the current density is increased from 1 to 15 mA cm(-2), an increase of a factor of 15. Based on mass loading, this corresponds to a very high gravimetric capacitance of 674 (for 2 mA cm(-2) or 1.48 Ag-1) and 444 Fg(1-) (for 15 mA cm(-2) or 11 A g(-1)) in a full-cell configuration with the Co0.85Se HNWs as cathode and activated carbon as anode (asymmetric configuration) promising results are obtained.
Keywords: asymmetric supercapacitor; carbon fiber paper; cobalt selenide; hydrothermal; pseudocapacitor; selenization

Single-step synthesis of exfoliated Ti3C2Tx MXene through NaBF4/HCl etching as electrode material for asymmetric supercapacitor - Ghosh, Meena; Szunerits, Sabine; Cao, Ning; Kurungot, Sreekumar; Boukherroub, Rabah (ChemistrySelect, 2022)
Two-dimensional Ti3C2Tx MXene, derived from the parent Ti3AlC2 phase, is considered a promising electrode material for electrochemical energy storage applications. Ti3C2Tx MXene synthesis methods often employ concentrated hydrofluoric acid (HF), which is harsh, corrosive, and hazardous to the environment. Herein, we report the preparation of Ti3C2Tx MXene following a new synthetic route under a mild reaction condition comprising an aqueous solution of NaBF4 and HCl. This etching environment at a moderate temperature of 130 degrees C effectively removes the Al layer of the Ti3AlC2 precursor, assisted by the in situ formed HF in the reaction medium. Electron microscopy images of the as-prepared Ti3C2Tx (MX-130) reveal a partially exfoliated nanosheet-like morphology. The material displays a specific capacitance of 262 F g(-1) (three-electrode assembly, 1 A g(-1), -0.85 to -0.25 V vs. Hg/Hg2SO4) in 1 M H2SO4 electrolyte. The achieved specific capacitance is superior to that of Ti3C2Tx prepared via the common HF-treatment (25 F g(-1)). Additionally, the potential application of the optimized MXene as a negative electrode material is demonstrated in a quasi-solid-state RuO2|MX-130 asymmetric supercapacitor device.
Keywords: asymmetric supercapacitor; Electrochemistry; Fluoride salt etchant; Layered electrode materials; Transition metal carbides

Ultra-fast electro-reduction and activation of graphene for high energy density wearable supercapacitor asymmetrically designed with MXene - Karim, Golam Masud; Dutta, Pronoy; Majumdar, Abhisek; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dambhare, Neha V.; Rath, Arup K.; Maiti, Uday Narayan (Carbon, 2023)
Controlled perforation of graphene is vital to surpass the performance of supercapacitors that rely on their pristine form. However, their practical utilization has been halted by energy-inefficient and lengthy processing. Here, we are reporting a pulse Joule heating strategy for on-site reduction and activation to realize a multimodal porous framework made of perforated graphene using millisecond current pulses. The multimodal porosity and surface functionalities of graphene were regulated at an ultrafast rate by passing a transient current. Asdeveloped ready-to-use electrode composed of nano-to-macro multimodal porosity displays high areal capacitance of 380.2 mF cm-2 in symmetric two-electrode configuration, which is nearly 1.6 times higher than the nonelectro activated counterpart. Furthermore, a high-performance wearable asymmetric supercapacitor with an areal energy density of 107.8 mu Wh cm-2 was realized using this multimodal porous graphene in combination with suitable negative electrodes made of MXene. High energy density, together with stable and repeatable performance of the wearable device for 10000 cycles of charge-discharge and 5000 cycles of bending, signifies the importance of the as-developed device for practical wearable applications. Direct, simple processing of electrodes and orders of magnitude lower cost-and-processing-time can make the process appealing for practical wearable and other energy storage applications.
Keywords: asymmetric supercapacitor; Graphene activation; Joule heating; Solid-state supercapacitor; Wearable device